Dual generator cluster transient stability assessment using swallowtail catastrophe theory - Bugis, Ismadi; Hassen Kareem, Maithem (Praise Worthy Prize, 2013)
In this paper swallowtail catastrophe is used to determine the transient stability regions. The bifurcation set represents the transient stability region in terms of power system transient parameters bounded by the transient stability limits. The system modelling is generalized in such, that the analysis could handle either one or any number of critical machines. This generalized model is then tested on a New England 39bus 10-machine power system. The results of the stability analysis done with the generalized method are compared with the time solution and the results were satisfactory. The transient stability regions determined are valid for any changes in loading conditions and fault location. This method is a good candidate for on-line assessment of transient stability of power systems.